Bayesian estimation of strong earthquakes in the Inner Messiniakos fault zone, southern Greece, based on seismological and geological data - Papoulia, J.; Stavrakakis, G.; Papanikolaou, D. (Journal of Seismology, 2001)
Statistical estimates of earthquake magnitudes are unreliable when based on very few historical data. Additional sources of information, such as geological data, are then necessary to update estimates of seismicity parameters. The Bayesian probability theory is a tool to combine prior information of seismicity obtained from geological data with historical observations. This theory is tested in the case of the Inner Messiniakos fault zone, southern Greece, for the estimation of the probability of occurrence of strong earthquakes. Prior estimates of seismicity are developed from slip rate measurements, obtained from offsets of geological formations, on the basis of both onshore and offshore neotectonic data. The analysis emphasizes the importance of the input seismicity parameters, particularly the significance of the upper bound magnitude in the estimation of the seismic potential of active faults
Keywords: Active faults; bayesian probability theory; seismic hazard; southern Greece